An accelerated route of glycerol carbonate formation from glycerol using waste boiler ash as catalyst - Mohd Hasbi, Ab. Rahim; Paroo Indran, Vidhyaa; Zuhaimi, Nor Ain Syuhada; Deraman, Mohd Asyrak; M. M., Yusoff; Gaanty Pragas, Maniam; Taufiq Yap, Yun-Hin (RSC, 2014)
Waste boiler ash was successfully utilised as catalyst for the direct synthesis of glycerol carbonate from glycerol and urea. A series of catalysts were prepared using various calcination temperatures. The physico-chemical properties of the catalysts have been investigated by using XRD, BET, TGA, FESEMEDX, ICP-MS, Hammett test and CO2-TPD. From the study it was found that boiler ash had significant catalytic activity towards conversion of glycerol into glycerol carbonate. It is believed that the potassium metal ion which detaches from potassium silicate had a major impact on the catalytic data where the potassium ion being a weak Lewis acid causes selective catalytic transformation of glycerol into glycerol carbonate. The mechanistic pathway through glycerol carbamate intermediate was confirmed through time online analysis study using 13C-NMR and ATR-FTIR, respectively. However, the selective transformation of glycerol carbamate into glycerol carbonate is reported to be different where it is formed in an accelerated manner. The highest catalytic activity resulted in an average percentage of 93.6 0.4% glycerol conversion, 90.1 1.0% glycerol carbonate selectivity and 84.3 1.1% glycerol carbonate yield. Besides, for the first time the novel idea of using waste material, specifically boiler ash, is proposed as a catalyst for synthesis of glycerol carbonate from glycerol and urea. The current research employed suggests an alternative route for proper disposal of waste boiler ash.